Comparison of cardiac dysfunction in thalassemia major patients using deferoxamine or deferiprone as an iron-chelating agent - Rosalina Josep; Pustika Amalia Wahidiiyat; Partini Trihono; Piprim Yanuarso (Indonesian Pediatric Society, 2012)
Background In thalassemia major (TM) patients, major mortalityis due to cardiac hemosiderosis. Several types of iron chelatingagent available recently are given to overcome this problemObjective To compare cardiac dysfunction in thalassemia majorpatients who used subcutaneous deferoxamine (DFO) to thosewho used oral deferiprone (DFP) as an ironô€†chelating agent.Methods This crossô€†sectional study was held at the ThalassemiaCenter, Department of Child Healthô€†Cipto MangunkusumoHospital (DCHô€†CMH), Jakarta. We included TM patients aged1Oô€†18 years Mth a mean preô€†transfused hemoglobin level of 2:.7g/dL in the prior year, and who had used DFO or DFP for atleast 1 year v.ith good compliance, at a standard dose of DFO at40-60 mg/kg/day for 5 days a week or DFP at 50-100 mg/kg/day.We excluded TM patients v.ith congenital heart disease or overtheart failure. Transô€†thoracal echocardiography was performed atthe Integrated Cardiac Service, CMH by a pediatric cardiologistusing the conventional method and tissue Doppler imaging (TD I)consecutively, and within 2 weeks of the subject's receiving apacked red blood cell (PREC) transfusion. The 57 TM subjectsconsisted of 19 DFO users and 38 DFP users.Results In our subjects, diastolic dysfunction was more commonlyseen than systolic dysfunction, especially moderate diastolicdysfunction. In the DFO group, diastolic dysfunction only wasdetected in 3/19 subjects, systolic dysfunction only in 1/19 subjects,and both diastolic and systolic dysfunction in 15/19 subjects. Noneof the DFO users had normal cardiac function. In the DFP group,diastolic dysfunction only was seen in 6/38 subjects, and bothdiastolic and systolic dysfunction in 30/38 subjects, while 2/38subjects had normal cardiac function.Conclusion Diastolic and/or systolic dysfunction was detected inthe majority of subjects, but with preserved global cardiac function.We found that cardiac dysfunction was not significantly different inthe two iron chelator groups. For all subjects, diastolic dysfunctionÂ was seen in 89% of cases, while systolic dysfunction was detectedin 77% of cases. [Paediatr Indones. 2012;52:272,9].